Characterization of fish gelatin-gum arabic complex coacervates as influenced by phase separation temperature - Anvari, Mohammad; Pan, Cheol-Ho; Yoon, Won-Byong; Chung, Donghwa (ELSEVIER, 2015)
The rheological and structural characteristics of fish gelatin (FG)-gum arabic (GA) complex coacervate phase, separated from an aqueous mixture of 1% FG and 1% GA at pH 3.5, were investigated as influenced by phase separation temperature. Decreasing the phase separation temperature from 40 to 10 degrees C lead to: (1) the formation of a coacervate phase with a larger volume fraction and higher biopolymer concentrations, which is more viscous, more structural resistant at low shear rates, more shear-thinning at high shear rates, and more condensed in microstructure, (2) a solid-like elastic behavior of the phase separated at 10 degrees C at a high oscillatory frequency, (3) the increase in gelling and melting temperatures of the coacervate phase (3.7-3.9 degrees C and 6.2-6.9 degrees C, respectively), (4) the formation of a more rigid and thermo-stable coacervate gel. The coacervate phase is regarded as a homogeneously networked biopolymer matrix dispersed with water vacuoles and its gel as a weak physical gel reinforced by FG-GA attractive electrostatic interactions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: RHEOLOGICAL PROPERTIES; SALT CONCENTRATION; WHEY PROTEINS; COLLAGEN; SKIN